Barriers and Predictors Associated With Accessing Oral Healthcare Among Patients With Cardiovascular Disease in Australia. Issue 3 (May 2019) - Sanchez, Paula; Salamonson, Yenna; Everett, Bronwyn; George, Ajesh
Abstract : Background: Periodontal disease is associated with cardiovascular disease, and patients should be aware of this risk and seek dental care. Objective: In this study, the authors sought to identify the barriers and predictors for seeking oral healthcare among patients with cardiovascular disease. Methods: With the use of a cross-sectional descriptive study design, 307 patients with cardiovascular disease attending cardiac rehabilitation/outpatient cardiac clinics were surveyed between 2016 and 2017 in Sydney, Australia. Survey items included the prevalence of accessing dental services and a new "barriers to seeking frequent dental care" scale. Results: Most respondents (81%) reported at least 1 oral health problem, yet only 10% received any oral health information and more than half (58%) saw a dentist in the preceding 12 months. The barriers to seeking frequent dental care scale was internally consistent (Cronbach's α = 0.82) with 2 subscales, identified as personal-related and system-related barriers to accessing oral healthcare. Respondents were more likely to have seen a dentist in the previous 12 months if they received oral health information (adjusted odds ratio [AOR], 5.08; 95% confidence interval [CI], 1.62–15.93), had private health insurance (AOR, 3.33; 95% CI, 1.91–5.83), reported low barriers (AOR, 2.68; 95% CI, 1.61–4.47), or were born overseas (AOR, 2.13; 95% CI, 1.25–3.63). Conclusions: The accessibility and affordability of dental care, as well as lack of oral health awareness, are key barriers and predictors for patients with cardiovascular disease accessing dental care. Greater emphasis on oral health is needed in the cardiac setting, along with appropriate dental referral pathways. Abstract : Supplemental digital content is available in the text.